The concept and features of trade relations as a subject of Trade Law - O. V. Panasiuk (Bulletin of Kharkiv National University of Internal Affairs)
It is established that Trade Law is a branch of law which regulates legal relations arising in the course of business activities, in particular, those related to the purchase and sale of goods and services, as well as other transactions related to the relevant processes. This branch of law contains legal rules that govern the establishment, registration, management and liquidation of enterprises, transactions, fair competition, consumer protection, intellectual property, patents and trademarks, and other aspects of business activities related to trading.